Islamic family education management in the digital era: An analysis of Nasihat Siti Budiman by Syekh Sulaiman Ar- Rasuli - Yudi Gucandra; Nunu Burhanuddin; Supratman Zakir; Putri Laila Ramadhani; Zulfani Sesmiarni; Hayati Hayati; Arif Rahmat Triasa (Indonesian Journal of Educational Management and Leadership, 2026)
This study aims to analyse the model of Islamic family education management contained in the novel Nasihat Siti Budiman by Syekh Sulaiman Ar-Rasuli (1938) and to examine how it relates to the challenges of family education in the digital age. The method used is a descriptive-analytical literature review, with the primary data source being the novel Nasihat Siti Budiman and secondary sources comprising literature on Islamic educational management, Islamic parenting, and studies on education in the digital age. The analysis was conducted in three stages: identification of educational management values, classification into management functions, and contextualization considering the challenges of the digital age. The research findings indicate that this novel contains a comprehensive family educational management system encompassing: (1) pre-school competency-based educational planning covering foundational knowledge of the Qur’an, fiqh, tawhid, as well as basic literacy and numeracy; (2) the organization of parental roles involving consultation with the kinship system as a model of collaborative governance; (3) the implementation of education through contextual guidance that integrates traditional and religious values; and (4) character-based evaluation covering moral conduct, life skills, and steadfastness of conviction. This model has proven relevant as a response to the crisis in family education management in the digital age, characterized by a lack of planning, weak character values, and a lack of integration of religious values into contemporary parenting practices.